KONTEKSTUALISASI BUDAYA SUNDA PADA SEKOLAH BERBUDAYA BETAWI DALAM KONTEKS PENGEMBANGAN SASTRA ANAK UNTUK MENINGKATKAN LITERASI BUDAYA DI SEKOLAH DASAR - marliana, panisa; Aryanto, Sani; Aulianesia, Bunga; Wibowo, Ari; Zalfah Nurullail, Anna (Journal of Professional Elementary Education, 2024)
Development of children's literature and the interrelation of gastronomic knowledge in the context of Sundanese culture as a basis for developing digestible books into novelties from the library research carried out. Therefore, the aim of this research is to provide a comprehensive overview of the process of developing children's literature teaching materials that contextualize Sundanese culture as an effort to increase cultural literacy in elementary school (SD) students. This research uses the library research method to reveal several research findings including: (1) Basic concepts of early literacy; (2) The decodable book as a manifestation of early literacy learning in elementary school; (3) Characteristics of the decodable book category (B2); (4) Urgency of Cultural Literacy; (5) Elements of Sundanese Culture (6) Gastronomy in the context of Sundanese Culture; (7) Development of the decodable book based on Local Sundanese Cultural Wisdom. The library research method is considered an appropriate method to support meta-analysis results in several relevant previous studies supported by various theoretical studies from various sources and supporting government policies related to the focus of this research. The results of the research conducted revealed that book development can be explicitly identified through BSKAP No.030/P/2022 concerning Guidelines for book leveling, although there has been no discussion comprehensively. The results of this literature study produce propositions that can be followed up in other, more complex research.